TRANSFORMATION OF PUBLIC PROCUREMENT OF INDUSTRIAL PRODUCTS TAKING INTO ACCOUNT THE ENVIRONMENTAL FACTOR - A. E. Gukasova; S. P. Kiseleva (Вестник университета)
Actual problems of industry and environmental aspects of their manifestation have been designated. To reduce the negative impact of industry on the environment, the authors suggest using public procurement tools. The main measures carried out by the state in the interests of ensuring environmental-oriented purchases of industrial products have been given. It has been proposed to expand the practice of using life-cycle contracts as the main way of state support for environmental-oriented procurement, which will subsequently allow you to use effectively available resources, taking into account the environmental factor. There is a large number of different methods for determining the stages of the product life cycle. An attempt was made in this article to describe the application of the environmental factor at each stage of the product life cycle using the example of industry.